High‐resolution ultrasound visualization of the deep branch of the ulnar nerve. Issue 6 (21st March 2017) - Riegler, Georg; Lieba‐Samal, Doris; Brugger, Peter C.; Pivec, Christopher; Platzgummer, Hannes; Vierhapper, Martin; Muschitz, Gabriela; Jengojan, Suren; Bodner, Gerd
ABSTRACT: Introduction : The value of imaging the deep branch of the ulnar nerve (DBUN) over its entire course has not been clarified. Therefore, this study evaluates the feasibility of visualizing the DBUN from its origin to the most distal point. Methods : We performed high‐resolution ultrasound (HRUS) with high‐frequency probes (18–22 MHZ ), HRUS‐guided ink marking, and consecutive dissection in 8 fresh cadaver hands. In both hands of 10 healthy volunteers (n = 20), the cross‐sectional area (CSA) was measured at 2 different locations (R1 and R2). Results : The DBUN was clearly visible in all anatomical specimens and in healthy volunteers. Dissection confirmed HRUS findings in all anatomical specimens. The mean CSA was 1.8 ± 0.5 mm 2 at R1 and 1.6 ± 0.4 mm 2 at R2. Discussion : This study confirms that the DBUN can be reliably visualized over its entire course with HRUS in anatomical specimens and in healthy volunteers. Muscle Nerve 56 : 1101–1107, 2017